Cars - Lasseter, John.; Wilson, Owen, 1968-; Newman, Paul, 1925-2008.; Hunt, Bonnie; Larry, the Cable Guy.; Marin, Cheech; Newman, Randy; Walt Disney Pictures; Pixar (Firm); Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Disney/Pixar ; Distributed by Buena Vista Home Entertainment, 2006)
Hotshot rookie race car Lightning McQueen is living life in the fast lane until he hits a detour on his way to the most important race of his life. Stranded in Radiator Springs, a forgotten town on old Route 66, he meets Sally, Mater, Doc Hudson, and a variety of quirky characters who help him discover that there's more to life than trophies and fame.
English track: Dolby digital 5.1 surround EX; Dolby digital 2.0.
Bonus features: 'Mater and the ghostlight'; 'One man band'; inspiration for 'Cars'; Deleted scenes; Sneak peek of 'Ratatouill; Easter egg.
Film editor, Ken Schretzmann ; music, Randy Newman ; production designers, William Cone, Bob Pauley ; visual effects supervisor, Jessica Giampietro McMackin ; directors of photography, Jeremy Lasky, Jean-Claude Kalache.
Voices: Owen Wilson, Paul Newman, Bonnie Hunt, Larry the Cable Guy, Cheech Marin, Tony Shalhoub, Guido Quaroni, Jenifer Lewis, Paul Dooley, Michael Wallis, George Carlin, Katherine Helmond, John Ratzenberger, Michael Keaton, Joe Ranft, Richard Petty.
MPAA rating: G.
DVD.
Keywords: Automobiles, Racing -- Juvenile drama; Friendship -- Juvenile drama; Cities and towns -- Juvenile drama; Films for the hearing impaired